Anomali Fatwa Majelis Ulama Indonesia dalam Sistem Hukum Indonesia: Telaah Hukum Responsif - Achmad, Dirga; Thamrin, Azlan (Institut Agama Islam Negeri Kerinci, 2024)
As an independent social organization, the Indonesian Council of Ulama (MUI) provides facultative religious opinions. However, the psychological response of society often elevates these opinions or fatwas beyond mere guidance, with many being formalized by the government into legislation, particularly in the fields of Islamic economics and finance. This article aims to elucidate the role of MUI fatwas within the social fabric and collective consciousness of Indonesian society, which is formally regulated by its own legal system. Employing a normative-empirical approach, this study finds that the MUI, as a social organization, is more accurately categorized as a Quasi NGO (Quango) rather than a typical NGO. MUI fatwas are not part of Indonesia's binding legal system; they are instead responsive, recommendatory, and facultative. Nonetheless, MUI fatwas play a significant role in regulating various aspects of Muslim community life, especially in the domains of muamalah, such as halal product certification, Islamic economics, and Islamic banking.